Heme Oxygenase-2 Localizes to Mitochondria and Regulates Hypoxic Responses in Hepatocytes. (12th April 2018) - Waltz, Paul K.; Kautza, Benjamin; Luciano, Jason; Dyer, Mitch; Stolz, Donna Beer; Loughran, Patricia; Neal, Matthew D.; Sperry, Jason L.; Rosengart, Matthew R.; Zuckerbraun, Brian S.
Abstract : Hypoxia occurs as a part of multiple disease states, including hemorrhagic shock. Adaptive responses occur within the cell to limit the consequences of hypoxia. This includes changes in mitochondrial respiration, stress-induced cell signaling, and gene expression that is regulated by hypoxia inducible factor-1 α (HIF-1 α ). Heme oxygenase-2 (HO-2) has been shown to be involved in oxygen sensing in several cell types. The purpose of these experiments was to test the hypothesis that HO-2 is a critical regulator of mitochondrial oxygen consumption and reactive oxygen species (ROS) production to influence hypoxia-adaptive responses such as HIF-1 α protein levels and JNK signaling. Methods and Results . In vitro studies were performed in primary mouse hepatocytes. HO-2, but not HO-1, was expressed in mitochondria at baseline. Decreased oxygen consumption and increased mitochondrial ROS production in response to hypoxia were dependent upon HO-2 expression. HO-2 expression regulated HIF-1 α and JNK signaling in a mitochondrial ROS-dependent manner. Furthermore, knockdown of HO-2 led to increased organ damage, systemic inflammation, tissue hypoxia, and shock in a murine model of hemorrhage and resuscitation. Conclusion . HO-2 signaling plays a role in hypoxic signaling and hemorrhagic shock. This pathway may be able to be harnessed for therapeutic effects.